IMPLEMENTASI KARAKTER DISIPLIN PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM KELAS VII DI SMP WAHID HASYIM MALANG - Elsa Al Khansa; Muhammad Sulistiono; Lia Nur Atiqoh Bela Dina (VICRATINA, 2022)
One of the demands of the nation’s needs is through discipline, where discipline is a strong foundation in developing the character of students at school. This pandemic period has an effect on the discipline of students at Wahid Hasyim Middle School. Therefore, teachers need to re-establish self discipline in studenst, this causes students discipline to be not optimal because they have not been in school form a long time. Discipline character can be inserted in the subject to see the deepening of students on the subjects that have been taught by the teacher. One of them is through the subject of Islamic religious education. The rearcher formulated the problem, namely the planning, implementation, and results of inculcating disciplined character in the VII grade Islamic religious education subject at Wahid Hasyim junior high school Malang. This study aims  to describe the planning, implementation, and results of inculcating disciplined character in the seventh grade Islamic religious education subject at Wahid Hasyim junior high school Malang. In this study using a qualitative approach. Researchers used several techniques in collecting data, namely observation, interviews and documentation. Based on the results of interviews, observations, and documentation that researchers have done in instilling disciplined character in Islamic religious education subjects for class VII, it can be said that it has been implemented well.